Sub-100-nm sized silver split ring resonator metamaterials with fundamental magnetic resonance in the middle visible spectrum - Tobing, Landobasa Y. M. (2014)
Split ring resonator (SRR) metamaterials working in the visible spectrum have great potential applications, but their fabrication is challenging due to the stringent requirements in the feature size and critical dimension. This paper reports fabrication and systematic characterization of silver SRRs with sub-100-nm sizes that can have magnetic resonance entering into the visible frequency spectrum. SRR size as small as ∼60 nm and fundamental magnetic resonance (LC-resonance) as short as ∼604 nm have been successfully demonstrated, which to the best of our knowledge represent the smallest fabricated SRR and the shortest LC-resonance based on SRR geometry. The resonance wavelengths of the LC and plasmon modes of the sub-100-nm SRRs are found to linearly decrease with SRR size. Excellent agreement between LC-model and experimental data is obtained when the capacitance of the sub-100-nm SRRs is interpreted as capacitance between two spheres instead of between two parallel plates.